[External concrete staircase, College Union] - P. K. Phillips::::::photographer::: (1974)
Concrete stairs on the southeast side of the Union's western building. There are also larger concrete stairs that connect the Union plaza to the second floor. A banner reads 'Tom Paine' on the second floor mezzanine railing.